2011
DOI: 10.1038/clpt.2010.320
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacogenetics Implementation Consortium Guidelines for Thiopurine Methyltransferase Genotype and Thiopurine Dosing

Abstract: Thiopurine methyltransferase (TPM T) activity exhibits monogenic co-dominant inheritance, with ethnic differences in the frequency of occurrence of variant alleles. With conventional thiopurine doses, homozygous TPMT-deficient patients (~1 in 178 to 1 in 3,736 individuals with two nonfunctional TPMT alleles) experience severe myelosuppression, 30–60% of individuals who are heterozygotes (~3–14% of the population) show moderate toxicity, and homozygous wildtype individuals (~86–97% of the population) show lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
418
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(425 citation statements)
references
References 33 publications
5
418
0
2
Order By: Relevance
“…A reduction to 10% of standard dose of 6-MP is recommended for individuals who are homozygous for the TPMT variant allele [Relling et al, 2011].…”
Section: B21 Polymorphisms That Influence Drug Pharmacokineticsmentioning
confidence: 99%
“…A reduction to 10% of standard dose of 6-MP is recommended for individuals who are homozygous for the TPMT variant allele [Relling et al, 2011].…”
Section: B21 Polymorphisms That Influence Drug Pharmacokineticsmentioning
confidence: 99%
“…In patients with homozygous normal phenotype or normal enzymatic activity thiopurines can be initiated at a normal dose, while in heterozygotes or in patients with intermediate enzymatic activity the initial dose should be reduced by 30-70%; in the rare cases of mutant homozygotes with low or absent enzymatic activity, this class of medications should be avoided [75].…”
Section: Thiopurine Metabolismmentioning
confidence: 99%
“…Of the drugegene pairs in Table 1, the pharmacogenomic relationships between irinotecan and UGT1A1 (for neutropenia risk) (Innocenti and Ratain, 2006), and 6-mercaptopurine/thioguanine and TPMT (for severe myelosuppression) (Relling et al, 2011) have the most consistent, strong supporting evidence in favor of their routine use. For UGT1A1 as an example, several prospective studies have demonstrated that patients with the high-risk genotypes (UGT1A1*28 and UGT1A1*6) are significantly more likely to experience neutropenia, with two of these studies corroborating the relationship with pharmacokinetic supportive data (Innocenti et al, 2004;Minami et al, 2007).…”
Section: Major Current Pharmacogenomic Findings In Oncologymentioning
confidence: 99%
“…In other words, if a patient is known to be at high (genetic) risk of toxicity from a drug at standard treatment doses, could the clinician still use that drug, but at a lower dose? Specific dose-reduction pharmacogenomic prescribing recommendations are, to our knowledge, not available for any oncology drugs except for the above-mentioned TPMT substrates (Relling et al, 2011). For irinotecan, a genotype-driven dosefinding study using pharmacogenomics showed that the recommended 180 mg/m 2 dose for irinotecan in the FOLFIRI regimen is considerably lower than what can be actually tolerated if patients with high-risk UGT1A1 genotypes are excluded (Toffoli et al, 2010).…”
Section: Special Considerations In Implementing Oncology Pharmacogenomentioning
confidence: 99%